2022
DOI: 10.2147/opth.s354692
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Demodex Blepharitis in US Eye Care Clinic Patients as Determined by Collarettes: A Pathognomonic Sign

Abstract: Purpose To evaluate the prevalence of Demodex blepharitis by its pathognomonic sign, collarettes, in patients presenting for any reason to eye care clinics in the United States. Patients and Methods In this retrospective study by 7 investigators at 6 eye care clinics, case records of consecutive patients who underwent a slit-lamp examination, regardless of chief complaint, were reviewed for Demodex blepharitis, as id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Lost work days and reduced productivity add another $55.4 billion in indirect costs. 42 Since Demodex blepharitis is as common as DED and there is substantial overlap of symptoms and clinical presentation with DED, 9 Demodex blepharitis is also expected to have a similar socioeconomic impact. 15 Although the economic burden of Demodex blepharitis was not evaluated, the findings related to multiple visits to eye care professionals and myriad treatments used, even if ineffective, suggest considerable direct costs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lost work days and reduced productivity add another $55.4 billion in indirect costs. 42 Since Demodex blepharitis is as common as DED and there is substantial overlap of symptoms and clinical presentation with DED, 9 Demodex blepharitis is also expected to have a similar socioeconomic impact. 15 Although the economic burden of Demodex blepharitis was not evaluated, the findings related to multiple visits to eye care professionals and myriad treatments used, even if ineffective, suggest considerable direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Two recent US studies have reported Demodex infestation rates of 55% and 58% based on the detection of mites following lash epilation or presence of collarettes (cylindrical dandruff), respectively, among patients presenting for eye examinations for varying reasons. 8,9 Since approximately 45 million US patients visit eye care professionals annually; it is estimated that 25 million Americans may have Demodex blepharitis. 10,11 Despite the high prevalence of Demodex blepharitis, patients with the condition may go undiagnosed or misdiagnosed for years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2005, Gao et al [2] found that 100% of the people with cylindrical dandruff in the eyelash had Demodex mites. There has been an increasing amount of evidence to support that Demodex is an important cause of blepharitis and related ocular surface diseases [3][4][5][6][7][8][9][10][11] . In 2018, Liang et al [12] reported that Demodex caused blepharitis-associated keratoconjunctivitis, and the extent of keratopathy was related to the severity of blepharitis.…”
Section: Introductionmentioning
confidence: 99%
“…13 Fifty-six percent of cataract patients in the Titan study had Demodex blepharitis. 14 Given the higher bacterial load in Demodex blepharitis patients compared with patients without the disease, 15 minimizing the risk of DOI: https://doi.org/10.17925/USOR.2022. 16.1.2 touchREVIEWS in Ophthalmology bacterial infection prior to surgery by screening for Demodex blepharitis is also important.…”
mentioning
confidence: 99%